The effects of bark beetle-fire disturbance interactions on post-disturbance forest regeneration - Fleming, Jean L., author; Sibold, Jason, advisor; Baron, Jill, committee member; Hobbs, N. Thompson, committee member (Colorado State University. Libraries, 2015)
Disturbances in forested ecosystems create ecological legacies that can affect future disturbances and these disturbance interactions influence post-disturbance establishment. In addition, disturbances can become compounded and cause drastic ecosystem changes including decreased post-disturbance establishment, regeneration of unexpected species assemblages, or shifts to alternative stable states. I studied the post-disturbance establishment of five tree species following two interacting disturbances, a bark beetle outbreak and a high-severity fire. The goal of my research was to identify the factors that influence post-disturbance seedling establishment, and to determine how bark beetle-fire interactions affect forest regeneration. I evaluated seedling establishment at 98 study sites across the Cow Creek fire in Rocky Mountain National Park. Two bark beetle species, mountain pine beetle (Dendroctonus ponderosae) and spruce beetle (Dendroctonus rufipennis), caused epidemic scale tree mortality in the five years before the fire. I created a Bayesian mixture model for each tree species to assess the independent variables that influenced the abundance of the species' establishment. The variables that influenced mean seedling abundance were different for each species. Forest age, distance to a seed source following the fire, and disturbance interactions affected the seedling abundance for most of the species. The presence of recent bark beetle activity had a measurable affect on post-disturbance establishment for three species. P. contorta and P. tremuloides mean abundance increased by a factor of 3.1 and 1.4, respectively, in areas with mountain pine beetle disturbance. The mean abundance of P. engelmannii seedlings was 3.8 times greater in areas where spruce beetle had caused tree mortality before the fire. This increase in seedling abundance in areas with bark beetle presence was independent of the other studied factors, including fire severity and elevation. The increased seeding abundance I recorded following bark beetle and fire disturbance suggests that interacting disturbances can increase the likelihood that forests will recover to their original species assemblages. The results of this study should be utilized to inform future forest management and to avoid unnecessary management action.
Keywords: disturbance interactions; disturbance; subalpine forest; regeneration; Rocky Mountains